(untitled)
The aphid fauna of the Apulian region (South-Eastern Italian peninsula) is composed of 243 species and subspecies. Most of the taxa were detected on the base of direct samplings; basic data are given for the individual collection and host plant species. Most taxa are of palaearctic origin, with prevailing South-European and Mediterranean clistribution. The following nine taxa are new records for the Italian aphid fauna: Chaetosiphella stipae H.R.L., Drepanosiphoniella aceris ssp. fugans Rem. & Lecl., Subsaltusaphis paniceae Qued., Aphis fabae ssp. mordvilkoi Born. & Jan., Rhopalosiphum rufulum Rich., Schizaphis agrostis H.R.L., Acyrthosiphon loti (Theob.), Uhlmannia singularis Born., and Uroleucon pulicariae H.R.L.; short biologica! and taJonolnical accounts are given on each of such taxon. , number=2, journal=Bollettino di zoologia agraria e bachicoltura, year=2024, month=Oct., pages=213–243